Sistem Informasi Akuntansi Penjualan Bahan Pokok Berbasis Web Pada Housemart Cirebon - Alya Fadia; Yudhistira Arie Wijaya (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2023)
Housemart Cirebon is a trading company engaged in staple goods located on Jalan Cideng Indah, Cirebon Regency - West Java. Cirebon Housemart provides basic ingredients from national brands ranging from household needs, baby products, to body and beauty care products. At present the business activities carried out are somewhat less effective. Sales, promotions and orders are still done manually, this is less effective because there is no detailed information on what products are being sold to buyers. . Recording and checking of transaction data, customer data, goods data, is still done manually in written document archives, data loss is still very likely to occur. The development method used to design the system uses the prototype method. The results of this research are in the form of a web-based Housemart Cirebon Sales Information System that is capable of performing sales, ordering and data processing services at Cirebon Housemart so that it can increase the effectiveness and efficiency of performance and time. The hope is to be able to provide complete information regarding the ordering process, services and promotions so that it is even better at Housemart Cirebon.